A comparative performance appraisal of rice farming by women collective farming units (JLG) under Kudumbashree Mission with individual farming units in Kerala: Analysis of rice farming under Kudumbashree Mission - Rosna , Aysha; Mishra , Sarba Narayan Mishra; Handral, Ankhila R; Das, Sarbani Das; Gupta , Akhilesh Kumar Gupta (ORYZA-An International Journal of Rice, 2025)
Rice (Oryza sativa) is one of the world’s most vital staple crops, serving as a primary source of sustenance for billions of people across the globe. This study was conducted with a goal to compare the performance and resource allocation of rice cultivation by women collective farmers in Joint Liability Groups (JLGs under Kudumbashree Mission) and individual farmers in Kerala and to analyse the constraints faced by the women collective farmers in rice farming. The study revealed that an additional unit of land would give the maximum additional yield of rice for collective farmers as well as individual farmers, ceteris paribus. In both collective and individual farming methods, machine labour, farmyard manure (FYM), and plant protection chemicals were underutilized resources, while human labour, and fertilizer were overutilized. Both the farming communities showed increasing returns to scale. The average experience of collective farmers in rice cultivation was considerably less than that of individual farmers, contributing to the lower productivity of collective farming. Additionally, the unavailability of good quality land for leasing also affected their yield. The main production constraint faced by collective farmers was pest and disease incidence followed by high wage rates for human labour. Low price for the crop in the market was the major marketing constraint faced by collective farmers.